réseau social pour l'apprentissage humain - BOULIF, Dalal ·; LALMI, Hana (university of eloued جامعة الوادي, 2014)
ھذا العمل مقدم لتخرج یركز على إنشاء شبكة اجتماعیة لتعلیم البشري یطلق على البرنامج المنجز اسم كما أ نھ یعرضواجھة بسیطة ومن أھم الوظائف ,(Réseau social pour l’apprentissage Humaine) التي تقدمھا الشبكات والتعلیم الالكتروني: - أداة للوصول إلى الشبكة على حسب المستخدم سوءا كان مدیرا أستاذا أو طالبا - یقدم الصفحات الشخصیة للأستاذ أو الطالب - إضافة حصصودروس وتمارین - الاستفادة من المراسلة (الشات) وھدفنا ھو تطویر طریقة تنفیذ التعلیم الالكترونيThis work is submitted for graduation focuses on the creation of a social network for the education of the human the program called (Réseau social pour l’apprentissage Humain). The program presents a simple interface and the most important jobs provided by the Social networks and e-learning: -A tool to the network depending on the user’s worse was director or a professor or a professor or a student. -Manage personal profiles for users. - Add lots of lessons and exercises. - Take advantage of the messaging (chat). Our goal is to develop a method of Execution of e-learning.
licence mémoire informatique